Perlakuan Pengabaian Pada Lansia Selama Menjalani Kehidupan Masa Tua di Panti Sosial Tresna Werdha (PSTW) - Septirina Rahayu; Novy H.C Daulima; Yossie Susanti Eka Putri (JOURNAL EDUCATIONAL OF NURSING(JEN), 2018)
Elderly people are vulnerable to violent behavior, forms of violence experienced by elderly people who living in the old age homes, one of which is the neglect. Behavior neglect of the elderly were found in the nursing home, suggests that there is a failure to provide elderly services needed by the caretaker. The purpose of this study to gain an overview of the behavior of the neglect of the elderly for living a life in old people’s homes. This study used a qualitative method with descriptive phenomenology approach. Participants in this study consisted of six elderly people who live in institutions. Data were collected through interviews in accordance with the purpose of research, and analysis of data from interviews using the analysis stage by Collaizi. The findings of this research, there are three themes, namely a decrease in self-reliance as a risk factor for neglect treatment, the unmet need by operators as a form of neglect in nursing, repression and suppression is an adaptive response to the neglect. The treatment of the neglect will affect the psychological condition of the elderly, which will ultimately affect th e health of the elderly. For that carers are expected to provide better services, provide a full treatment of attention and affection so that quality of life of the elderly in nursing can be achieved. Recommendations from this study, the nurses, especially nurses psychiatric specialist can pay attention, to detect as early as possible behavioral changes experienced by the elderly and implement appropriate therapy spsesialis nurses with nursing diagnoses were found. Keywords: Elderly, Nursing home, Neglect.